Panorama do campo de estudo da Rede Federal de Educação Profissional, Científica e Tecnológica do Brasil (2009-2018) - Oliveira, Greissi Gomes (Universidade Federal de São Carlos, 2020)
The theme of this research is professional, scientific and technological education in Brazil. Its object of study is the Federal Network for Professional, Scientific and Technological Education (RFEPCT), established in 2008, seen from the stricto sensu research. The RFEPCT, by law, must offer different courses acting from the initial training of workers to post-graduation. It should also have its activities developed in the Teaching-Research-Extension triad and is composed of several institutions that total 650 units and 9 innovation hubs (until October 2018). In this context, the following questions arose: how have stricto sensu researches been set up regarding the institutions of the Federal Network for Professional, Scientific and Technological Education in Brazil, based on Law No. 11,892, of December 29, 2008? In the teaching, research and extension triad, which aspect has received more prominence in research that addresses the RFEPCT institutions? Among the different levels of education (higher, secondary, technical, initial and continuing education) that the Law determines that these institutions act, which ones have received more attention in the studies developed in graduate studies in Brazil, when it comes to the RFEPCT institutions? Our hypotheses for these questions are: a) within the scope of the triad of teaching, research and extension, teaching has a greater chance of receiving attention in research on the RFEPCT institutions, due to the origin of the institutions having occurred from this aspect; b) because they have a greater number of institutions and campuses and because they are a recent institution, Institutes should receive greater attention as objects or contexts of research studies; c) even with the deliberation in the legislation of the offer of several levels, the technical vocational education of medium level must appear in more number of studies in the stricto sensu researches that approach the institutions of the RFEPCT. Based on the issues raised in this research, the general objective is to present an overview of the stricto sensu field of studies of the Federal Network of Professional, Scientific and Technological Education in Brazil in the period from 2009 to 2018. The specific objectives are: a) to analyze the production on professional, scientific and technological education in the CAPES Catalog of Theses and Dissertations regarding the variables: assessment areas, gender of researchers, Institution, Postgraduate Program (PPG), methodologies, study participants, funding agency, year of defense; b) to identify the presence of institutions belonging to the Network in the research carried out in this field; c) identify the extent to which teaching, research and extension aspects have been addressed in studies on the institutions of the Network; d) identify the extent to which the different levels of education have received attention when it comes to stricto sensu research on the Network or its institutions; e) systematically map stricto sensu scientific production on the institutions that make up the RFEPCT. According to the selection criteria, 38 theses were selected and analyzed. The results obtained were: the theses are developed in 32 graduate programs; there is a prevalence of authors and advisors; qualitative methodologies are present in most studies; the main study participants are teachers; the main funding agency is CAPES; there is a sharp growth in production in 2018. The institutions that are in the largest number of studies as locus are the Federal Institutes; the teaching aspect is the most addressed in research; the most approached level of education was higher, with the degree courses prevailing.
Overview of the field of study of the Federal Network of Professional, Scientific and Technological Education in Brazil (2009-2018)
Panorama del campo de estudio de la Red Federal de Educación Profesional, Científica y Tecnológica de Brasil (2009-2018)
Keywords: Rede Federal de Educação Profissional, Científica e Tecnológica; Instituto Federal; CEFET; Colégio Pedro II; Escolas técnicas vinculadas às universidades; Bibliometria; Estado do conhecimento; Federal Network of Professional, Scientific and Technological Education; Federal Institute; Technical schools linked to universities; Bibliometrics; State of knowledge; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO